Gamification in a Democratic Pro-Environmental Behaviour Model Towards Achieving Effective ESG Corporate Strategies - Markopoulos Evangelos; Vera Ramirez Alejandro; Markopoulos Panagiotis; Vanharanta Hannu (United States, 2022)
This paper aims to analyze the extent to which gamification is an effective alternative to promote the adoption of democratic pro-environmental behaviors and contribute towards the creation of the relative organization culture. The accepted definition of gamification for this paper is the process of enhancing a service with affordances for gameful experiences to support users’ overall value creation. This marketing perspective approach focuses more on the effects obtained as a consequence of activating intrinsic and extrinsic motivation through gamified systems rather than the analysis of the characteristics of the game design elements and the incentives for its practical and actual adaptation and utilization within organizations. Furthermore, the proposed model is linked with the ESG criteria to further incentivize its organization’s adaptation from theory to practice. Finally, the paper indicates limitations and areas of further research towards green ocean strategies that can maximize its applications and impact.
Creativity, Innovation and Entrepreneurship: Proceedings of the 13th AHFE International Conference on Creativity, Innovation and Entrepreneurship, New York, USA July 24-28, 2022